1990
DOI: 10.1161/01.cir.82.6.1973
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic effects of angiotensin II on human cardiac muscle in vitro.

Abstract: The direct effects of angiotensin II (Ang II) on human cardiac muscle were investigated using isolated trabecular muscles from failing and functionally normal hearts. (Circulation 1990;82:1973-1984 T wo developments in the field of cardiovascular physiology have renewed interest in the effects of angiotensin II (Ang II) on the myocardium. First, the observation that angiotensin converting enzyme inhibitors such as captopril are more efficacious in treating heart failure patients than direct-acting vasodilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 54 publications
4
54
1
1
Order By: Relevance
“…As clearly shown in the results, L-158,809 potently suppressed the angiotensin II-induced vasopressor response, with a potency similar to those reported previously (7). We also confirmed the angiotensin II-induced negative inotropic effect in this study, although the substance has been reported to exert positive (8), no (9), negative (10), or biphasic inotropic effects (11). L-158,809 attenuated the angiotensin II-induced negative inotropic response in a dose-related manner, which has not been reported elsewhere.…”
supporting
confidence: 90%
“…As clearly shown in the results, L-158,809 potently suppressed the angiotensin II-induced vasopressor response, with a potency similar to those reported previously (7). We also confirmed the angiotensin II-induced negative inotropic effect in this study, although the substance has been reported to exert positive (8), no (9), negative (10), or biphasic inotropic effects (11). L-158,809 attenuated the angiotensin II-induced negative inotropic response in a dose-related manner, which has not been reported elsewhere.…”
supporting
confidence: 90%
“…Several previous studies have shown that PoAT correlates closely with mean pulmonary arterial pressure and pulmonary vascular resistance [13][14][15] be supported by in vitro data showing that angiotensin II produces positive inotropic effects in the isolated heart [19,20]. Since angiotensin II also produces right ventricular preload reduction by venodilatation [12], the net effect on PoAcc is probably a summation of responses.…”
Section: Discussionmentioning
confidence: 81%
“…Angiotensin II (AII) elicits a positive inotropic effect (PIE) in the cardiac muscles of certain mammalian species that include man (Moravec et al, 1990) and the rabbit (Dempsey et al, 1971;Freer et al, 1976;Ishihata & Endoh, 1993). Direct activation of specific receptors by AII is considered to trigger a signal-transduction process that results in the PIE (Dempsey et al, 1971;Freer et al, 1976;Kobayashi et al, 1978;Moravec et al, 1990).…”
Section: Introductionmentioning
confidence: 99%